Prim´s murder through the spanish press at the end of 1870 (Estudios de Historia de España, 2021)
The attempt that finished with the life of the president of the Council of Ministers, Juan Prim y Prats (1814-1870), continues being a mystery. The identity and the modus operandi of those who organized, financed and instigated the crime are still under discussion. This work is focus on the analysis of the press of the moment of the crime with the aim of analysing the known details moments just after the attempt occurred and how this information was transmitted to the Spanish society.
Keywords: Prim; Crime; Press; Information; News